A simple model for GPS C/A‐code self‐interference. Issue 2 (7th June 2020) - Hegarty, Christopher J.
Abstract: The GPS C/A‐code is the most widely utilized GNSS signal today. The C/A‐code design includes (1) a short (length‐1023) spreading code that repeats every 1 ms and (2) a low (50 bps) data rate. These two characteristics can lead to undesired interactions between received C/A‐code signals within user equipment. In this paper, a simple model is derived for predicting the impact of C/A‐code self‐interference on receiver performance. The accuracy of the model in predicting C/A‐code self‐interference is assessed through the use of a high‐fidelity GPS receiver software simulation.